Von-Willebrand factor as a predictor of three-month mortality in patients with liver cirrhosis compared to MELD score - Curakova Ristovska, Elena; Genadieva Dimitrova, Magdalena; Caloska-Ivanova Viktorija; Misevski Jane (Universa Press, 2019)
Introduction and aim : Endothelial dysfunction is involved in the pathogenesis of portal hypertension and in the progression of liver disease. As an indicator of endothelial dysfunction, von Willebrand factor (vWF-Ag) can be a useful mortality predictor in patients with liver cirrhosis. The aim of the study is to compare the predictive value of vWF-Ag with the predictive value of MELD score regarding the three-month mortality in patients with liver cirrhosis. Materials and methods : In 70 patients with cirrhosis and portal hypertension we measured the vWF-Ag concentration and we followed the patients for 90 days. We registered all manifestations and complications of liver cirrhosis and the three-month mortality was the main end-point. Results : We registered mean vWF-Ag of 341.9±155.8%, median 312%, IQR (214-410), vWF-Ag significantly correlated with MELD score (R=0.3713 ; p<0.05) and vWF-Ag median was higher in the uncensored compared to the median in the censored patients (p<0.0067). vWF-Ag and MELD score were significantly associated with three-month mortality, with no significant difference in the diagnostic performance between the two parameters [AUC=0.735, p=0.007 for vWF-Ag ; AUC=0.885, p=0.000 for MELD score], (Z=-1.473, p=0.1407). Conclusion : In patients with liver cirrhosis vWF-Ag is a relevant predictor of three-month mortality that equals the MELD score.
Keywords: von-Willebrand factor; mortality; cirrhosis; endothelial dysfunction